2015
DOI: 10.24218/jod.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Apoptosis, Advanced Glycation End Products and Transforming Growth Factor-β1 by Biguanides and Resveratrol to Ameliorate Experimentally-induced Diabetic Nephropathy

Abstract: Background: Diabetic nephropathy is one of the complications of diabetes caused by angiopathy of capillaries in the renalglomeruli. Its mechanisms may include glycosylation of renal proteins, abnormal intrarenal hemodynamics and hypertension. Resveratrol is a natural compound found in grapes and red wine that offers protective effects against many cardiovascular diseases and cancer. Metformin is a biguanide that is considered as the first-line drug for treatment of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ciddi et al showed that 10 mg/kg/d of oral RSV supplementation for 3 weeks reduced AGE formation in diabetic rats . Kabel et al demonstrated that oral administration of RSV (5 mg/kg/d) alone or in combination with metformin for 8 weeks considerably decreased AGE formation in a rat model of STZ‐induced diabetic nephropathy . Yılmaz et al found a significant reduction in the levels of plasma AGE in MGO‐treated rats received 10 mg/kg of RSV via injection compared to the control group .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciddi et al showed that 10 mg/kg/d of oral RSV supplementation for 3 weeks reduced AGE formation in diabetic rats . Kabel et al demonstrated that oral administration of RSV (5 mg/kg/d) alone or in combination with metformin for 8 weeks considerably decreased AGE formation in a rat model of STZ‐induced diabetic nephropathy . Yılmaz et al found a significant reduction in the levels of plasma AGE in MGO‐treated rats received 10 mg/kg of RSV via injection compared to the control group .…”
Section: Resultsmentioning
confidence: 99%
“…33 Kabel et al demonstrated that oral administration of RSV (5 mg/kg/d) alone or in combination with metformin for 8 weeks considerably decreased AGE formation in a rat model of STZ-induced diabetic nephropathy. 35 Yılmaz et al found a significant reduction in the levels of plasma AGE in MGO-treated rats received 10 mg/kg of RSV via injection compared to the control group. 24 The authors also stated that treatment with RSV reduced the productions of protein carbonyl and advanced oxidation protein products.…”
Section: Effect Of Rsv On the Generation Of Agesmentioning
confidence: 97%
“…erefore, targeting myocardial apoptosis may be an effective target for patients with diabetic cardiomyopathy. H9c2 cardiomyocytes are a cell line derived from an embryonic rat heart whose biological functions are similar to those of primary cardiomyocytes [28]. Nevertheless, it is unclear whether RES can protect the H9c2 cells from HG-stimulated damage.…”
Section: Discussionmentioning
confidence: 99%